UK Guidelines on the Diagnosis and Treatment of Breast Implant‐Associated Anaplastic Large Cell Lymphoma on behalf of the Medicines and Healthcare products Regulatory Agency Plastic, Reconstructive and Aesthetic Surgery Expert Advisory Group. (22nd November 2020) - Turton, Philip; El‐Sharkawi, Dima; Lyburn, Iain; Sharma, Bhupinder; Mahalingam, Preethika; Turner, Suzanne D.; MacNeill, Fiona; Johnson, Laura; Hamilton, Stephen; Burton, Cathy; Mercer, Nigel
Summary: Breast implant‐associated anaplastic large cell lymphoma (BIA‐ALCL) is an uncommon T‐cell non‐Hodgkin Lymphoma (NHL) associated with breast implants. Raising awareness of the possibility of BIA‐ALCL in anyone with breast implants and new breast symptoms is crucial to early diagnosis. The tumour begins on the inner aspect of the peri‐implant capsule causing an effusion, or less commonly a tissue mass to form within the capsule, which may spread locally or to more distant sites in the body. Diagnosis is usually made by cytological, immunohistochemical and immunophenotypic evaluation of the aspirated peri‐implant fluid: pleomorphic lymphocytes are characteristically anaplastic lymphoma kinase (ALK)‐negative and strongly positive for CD30. BIA‐ALCL is indolent in most patients but can progress rapidly. Surgical removal of the implant with the intact surrounding capsule (total en‐bloc capsulectomy) is usually curative. Late diagnosis may require more radical surgery and systemic therapies and although these are usually successful, poor outcomes and deaths have been reported. By adopting a structured approach, as suggested in these guidelines, early diagnosis and successful treatment will minimise the need for systemic treatments, reduce morbidity and the risk of poor outcomes.